2006
DOI: 10.1111/j.1349-7006.2006.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signal pathway is activated in ovarian carcinomas, correlating with cell proliferation: It's inhibition leads to growth suppression and apoptosis

Abstract: The hedgehog (Hh) signal pathway has recently been shown to be activated in human malignancies. However, little is known about its role in the development or patient prognosis of epithelial ovarian carcinoma. In the present study, we examined in vivo and in vitro E pithelial ovarian carcinoma, which comprises the majority of malignant ovarian tumors, is the leading cause of death from gynecologic malignancy in women.(1) The survival of ovarian carcinoma patients has not improved significantly for years, indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
133
2
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(151 citation statements)
references
References 32 publications
12
133
2
4
Order By: Relevance
“…SHH is active only in stem cells and/or endodermal progenitor in adults (16,23). Recent studies showed that aberrant signaling of this pathway is involved in a variety of human cancers (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). The HH pathway essentially consists of PTCH, the motive protein, SMOH, and the transcriptional factors GLI2 and GLI3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SHH is active only in stem cells and/or endodermal progenitor in adults (16,23). Recent studies showed that aberrant signaling of this pathway is involved in a variety of human cancers (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). The HH pathway essentially consists of PTCH, the motive protein, SMOH, and the transcriptional factors GLI2 and GLI3.…”
Section: Discussionmentioning
confidence: 99%
“…The HH activation has been observed in other types cancers such as basal cell carcinomas of the skin (6-9), prostate cancer (10,11), lung cancer (12,13), gastrointestinal cancers (14)(15)(16)(17)(18)(19), breast cancer (20,21), and ovarian cancer (22). Although, it is required in liver embryogenesis (14,23), the HH signaling pathway is not well-sustained in the adult liver because of the insufficient HH pathway activity of mature hepatocytes (1,23).…”
mentioning
confidence: 99%
“…Abnormal signaling of this pathway has been reported in a variety of human diseases, including cancer and neurodevelopmental diseases. For example, chronic Hh pathway stimulation is observed in prostate cancer (2)(3)(4), lung cancer (5,6), and ovarian cancer (7,8) in a Hh ligand-dependent manner. Recently, serum levels of Hh ligand protein were found to be significantly higher in children with autism spectrum disorder (ASD) and the levels of Hh ligand were correlated with the severity of autism (9).…”
mentioning
confidence: 99%
“…Hh signaling depends on a fine-tuned intracellular signal mediated by the repressor or activator forms of the transcription factors GLI2 and GLI3, and is mainly based on a positive feedback loop via GLI1 and a negative feedback loop via Patched-1 (PTCH1) transcription [24,25]. It is, in particular, these feedback loops that are found disturbed in EOC specimens [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Further, a number of recent studies have indicated that EOC is linked to aberrant cell signaling, including Hedgehog (Hh) and platelet-derived growth factor (PDGF) signaling as well as over-expression of aurora A kinase (AURA) and deregulated expression of the novel tumor suppressor protein, checkpoint with forkhead-associated and ring finger domains (CHFR) [7][8][9][10][11][12][13][14][15][16][17][18][19]. Consequently, targeted agents against Hh pathway components, PDGFR and AURA have been explored recently in the management of ovarian cancer and recurrent disease [20].…”
Section: Introductionmentioning
confidence: 99%